A practical writing guide for academic librarians : keeping it short and sweet - Langley, Anne (Chandos information professional series., 2010)
This text helps academic librarians make their writing for for work go more smoothly. From progress reports to project plans, cover letters to case studies, book reviews to blogging, readers will find examples and how-tos for most of the types of writing they will need to do in their academic library careers.